Comparison of Predicted Complexity of Coronary Lesions with Duke Treadmill Score on Various Risk Factors for Coronary Heart Disease - D Rubiyaktho (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: According to Framingham Study, independent risk factors for coronary heart.....